EFEKTIVITAS MODEL KOOPERATIF MAKE A MATCH TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SDN MANGKUBUMEN WETAN KELAS III - Rachmwati Salsa Azariai; Ema Butsi Prihastari; Jumanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to investigate how well the cooperative learning model 'Make a Match' enhances students' problem-solving abilities in mathematics. The background for this study is the low competency of students resulting from traditional methods. The methodology employed is quantitative with a One Group Pretest- Posttest design, involving 30 students. Data were collected through tests, observations, and documentation. The results indicate an improvement in average scores from 59.67 to 84.50, categorized as a moderate N-Gain. The t-test reveals a significant increase (p = 0.000). These findings suggest that the Make a Match model is effective in improving students' abilities and participation.